2015
DOI: 10.1186/s12935-015-0250-9
|View full text |Cite
|
Sign up to set email alerts
|

Eukaryotic translation initiation factor 5A2 (eIF5A2) regulates chemoresistance in colorectal cancer through epithelial mesenchymal transition

Abstract: BackgroundChemoresistance is a major obstacle to successful chemotherapy for colorectal cancer. Eukaryotic translation initiation factor 5A2 (eIF5A2), one of the two isoforms in the eIF5A family, has been reported to be a new oncogene in many types of human cancer. In the present study, we aimed to investigate whether eIF5A2 was involved in the chemoresistance to doxorubicin in colorectal cancer.MethodsCell viability was measured by CCK-8 assay with or without doxorubicin treatment. Protein expression was dete… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(46 citation statements)
references
References 30 publications
1
44
0
1
Order By: Relevance
“…In the present study, we demonstrated that a series of doses of TGFβ1 stimulation (2, 5, 10 ng/ml) could promote the protein levels of EIF3A and mesenchymal marker Vimentin, reduce the protein level of epithelial marker E‐cadherin, and the acquisition of an EMT phenotype; shRNA‐induced EIF3A knockdown could suppress TGFβ1‐induced EMT‐related changes, and partially reverse the effect of TGFβ1 on EMT. According to previous studies, eukaryotic translation initiation factor 5A2 (eIF5A2), one of the two isoforms in the eIF5A family, is involved in regulation of the EMT during the chemoresistance to doxorubicin [Bao et al, ]. In our previous study, we demonstrated that EIF3A plays an important role in bleomycin‐induced pulmonary fibrosis by regulating pulmonary fibroblasts’ function, and up‐regulation of eIF3a induced by TGFβ1 is mediated via the ERK1/2 pathway [Li et al, ].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…In the present study, we demonstrated that a series of doses of TGFβ1 stimulation (2, 5, 10 ng/ml) could promote the protein levels of EIF3A and mesenchymal marker Vimentin, reduce the protein level of epithelial marker E‐cadherin, and the acquisition of an EMT phenotype; shRNA‐induced EIF3A knockdown could suppress TGFβ1‐induced EMT‐related changes, and partially reverse the effect of TGFβ1 on EMT. According to previous studies, eukaryotic translation initiation factor 5A2 (eIF5A2), one of the two isoforms in the eIF5A family, is involved in regulation of the EMT during the chemoresistance to doxorubicin [Bao et al, ]. In our previous study, we demonstrated that EIF3A plays an important role in bleomycin‐induced pulmonary fibrosis by regulating pulmonary fibroblasts’ function, and up‐regulation of eIF3a induced by TGFβ1 is mediated via the ERK1/2 pathway [Li et al, ].…”
Section: Discussionmentioning
confidence: 93%
“…translation initiation factor 5A2 (eIF5A2), one of the two isoforms in the eIF5A family, is involved in regulation of the EMT during the chemoresistance to doxorubicin [Bao et al, 2015]. In our previous study, we demonstrated that EIF3A plays an important role in bleomycin-induced pulmonary fibrosis by regulating pulmonary fibroblasts' function, and up-regulation of eIF3a induced by TGFb1 is mediated via the ERK1/2 pathway [Li et al, 2015c].…”
Section: Journal Of Cellular Biochemistrymentioning
confidence: 99%
“…The downregulation of miR-125b causes the overexpression of EIF5A2, which is known to be associated with proliferation and poor prognosis in patients with CRC and NSCLC. 39,[69][70][71] MiR-100 reduces the protein level of Angpt2, which is an essential molecule for angiogenesis, by blocking the mTOR/p70S6K signaling pathway. It has been demonstrated that miR-125b can cause excessive angiogenesis by affecting the proliferation of endothelial cells.…”
Section: Downregulation Of Mir-125b In Cancermentioning
confidence: 99%
“…Previous studies have demonstrated that EIF5A2 exhibits its tumorigenic effects via activation of the phosphoinositide-3-kinase/Rac-α serine/threonine-protein kinase signaling pathway (15,25) and its induction of matrix metalloproteinase 2 protein expression (26). In addition, EIF5A2 reduces expression of E-cadherin and increases expression of Vimentin (26,27), and may activate transforming protein RhoA precursor/Rac1 signaling pathways (24). Additionally, a previous study identified zinc finger protein Gli1 as a putative transcription factor for EIF5A2 (28).…”
Section: Discussionmentioning
confidence: 99%